Art Therapy for Client with Substance Abuse - Cucu Rokayah; Resnizar Annasrul; Raden Wulan W. (Universitas Muhammadiyah Semarang, 2020)
Drug abuse in Indonesia is increasing from year to year, from the age of 15 to 64 years using narcotics at least one a year and the need to be aware of proliferation of new types of narcotics. One way of helping in the recovery of people with drug abuse. Purpose is to describe the client’s art therapy due to drug abuse. The writing method used in this writing is a journal-based literature review, with several stage, : determining the big topic, journal screening and determining the theme of the journal references obtained. Art therapy which is effective for drug use is by using painting therapy and musik therapy. Painting as therapy, is related to the contemplative or sublimation aspects so thar it can express feelings and reduce dependence on subtances. In conclusion, art therapy is needed by clients with mental disorders, especially female and adolescent clients. Art therapy is a means of channeling thoughts and feelings that a client with drug abuse may not be able to verbalize.